Impact of Commitment to Psychological Well-being among Students Who are Undergoing Long-Distance Relationship - S.G.M. Welvart; A. Huwae (Moscow State University of Psychology and Education, 2024)
The phenomenon of long-distance relationships among students that have developed in this era is an opportunity that allowed them to thrive optimally in maintaining their relationships. However, in fact, LDR for students is still a challenge in itself because it requires a greater effort that can affect the achievement of individual psychological well-being. Psychological well-being is a necessary condition for individuals, including students who are in long-distance relationships so that they are able to maintain relationships optimally. Psychological well-being can be achieved by the presence of various factors, one of which is commitment. This study aims to determine the relationship between commitment and psychological well-being in students who are in long-distance relationships. The method used in this research is correlational quantitative. 587 students are undergoing long-distance relationships to become participants in this study with the accidental sample as the sampling technique. This study used two scales The Revised Commitment Inventory and the Ryff Scale of Psychological Well-being. The hypothesis test results with the Pearson correlation were 0,987 with sig = 0,000 (p<0,01), which means that the research hypothesis was accepted. Commitment contributed 97,4% to psychological well-being. This research shows that commitment is a very strong factor related to achieving psychological well-being in students who are in long-distance relationships. Commitment is essential in helping students to maintain relationships with existing different conditions while maintaining their psychological well-being and still carrying out their academic role optimally.